Financial Performance Analysis of Islamic Banks in Indonesia Based on Maqashid Sharia Index - Suryani, Putri; Amalia, Alvien Nur (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research was conducted to analyze how the financial performance of Islamic banks both individually and as a whole, based on the Maqashid Sharia used by Asy-Syatibi in terms of the purpose of educating individuals, the purpose of establishing justice, and the purpose of public interest during 2016-2020. The benefits of the results of this study can be used as consideration for many parties, including investors, creditors, customers, employees, regulators, and the surrounding community in making decisions by looking at how far the achievement of Islamic banking performance and compliance with Islamic principles in its operational activities. The type of research used is descriptive quantitative with the object of research conducted on 14 Indonesian Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK). The type of data used is secondary data in the form of financial reports/annual reports obtained from the official website of each bank and in the calculation using Simple Additive Weighting (SAW). The results of this research indicate that Bank Muamalat obtains the highest index for the purpose of educating individuals, Bank Victoria Syariah obtains the highest index for the purpose of establishing justice, and Bank Syariah Mandiri obtains the highest index for the public interest. As for the overall maqashid sharia index, Bank Syariah Mandiri has the highest score compared to thirteen other Islamic banks.